Grotta Mora Cavorso: Physical, material and symbolic boundaries of life and death practices in a Neolithic cave of central Italy. (20th February 2020) - Silvestri, L.; Achino, K.F.; Gatta, M.; Rolfo, M.F.; Salari, L.
Abstract: Grotta Mora Cavorso is a multi-stratified site located in the inner Apennines in Central Italy. The archaeological deposit found in it spans from Upper Palaeolithic to World War II, and holds one of the largest Neolithic burial deposits currently known in Italy. This work will seek to analyse and interconnect all the pieces of evidence collected during ten years of multidisciplinary investigation at the site, in order to understand several aspects of this peculiar anthropized cave and the wider implications in the whole of the Italian and Mediterranean region, with a specific focus on Neolithic occupation. First of all, we will integrate the data coming from three distinct sectors of the cave which appear to have been used in different ways (Entrance Room for everyday-life activities, Intermediate Room for rituals and Inner Rooms for burials), in the attempt to understand the links between these spaces and to draw a complete picture of the life and death practices during the late 6th millennium BC at Grotta Mora Cavorso. Secondly, through the unique dataset of artefactual, ecofactual, molecular and geological data provided by this cave, we will explore the meaning of such practices in the early Neolithic of Italy and the Mediterranean basin. By combining the DNA, isotope, demographic and morphological data coming from the study of the 28 individuals buried in the cave, we will try to find out whether social selection was already occurring at the time. In addition, spatial studies will allow us to clarify if funerary rituals were disconnected from everyday life or if there was a conceptual and practical continuity between these two aspects of human life. As a final aim for this work, we intend to use Grotta Mora Cavorso and its archaeological potential as an example on how to successfully integrate science and social studies in archaeology, in order to reach deeper understandings of human behaviour in prehistory.